KONDISI SOSIAL SEBAGAI DASAR TEORI SOSIOLOGI PENDIDIKAN - Puspita, Dhany; Abbas, Ngatmin (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2024)
This study aims to identify how social conditions serve as a primary factor in the formation of early theories of educational sociology. The background of this research lies in the significant social changes during the Industrial Revolution and the development of capitalism, which created a need to understand the role of education within social structures. Early sociological thinkers, such as Émile Durkheim and Karl Marx, argued that education is not merely a process of knowledge transfer but also a tool for maintaining social stability or fostering change. They saw education as a means to shape values and norms aligned with the economic and political needs of society. This research uses a descriptive qualitative method with a literature review approach. The data collected are derived from classical sociological literature and various modern studies that examine social conditions influencing the development of educational sociology theories. Data analysis is conducted with a historical approach to link educational theories with the social contexts that underpin them. The findings indicate that social conditions, such as class differences, economic changes, and labor demands, influence the educational goals discussed in sociology. Education is viewed as a tool for regulating social structure through the inculcation of values that benefit the dominant class. This study reveals that early educational sociology thought was closely tied to the social context that shaped it and often functioned either to maintain social stability or to drive change according to societal needs.